Mild behavioral impairment in early Alzheimer's disease and its association with APOE and BDNF risk genetic polymorphisms - Matuskova, Veronika; Veverova, Katerina; Jester, Dylan J; Matoska, Vaclav; Ismail, Zahinoor; Sheardova, Katerina; Horakova, Hana; Cerman, Jiri; Laczó, Jan; Andel, Ross; Hort, Jakub; Vyhnalek, Martin (Alzheimer's research & therapy, 2024)
BACKGROUND: Mild behavioral impairment (MBI) has been commonly reported in early Alzheimer's disease (AD) but rarely using biomarker-defined samples. It is also unclear whether genetic polymorphisms influence MBI in such individuals. We thus aimed to examine the association between the cognitive status of participants (amnestic mild cognitive impairment (aMCI-AD) vs cognitively normal (CN) older adults) and MBI severity. Within aMCI-AD, we further examined the association between APOE and BDNF risk genetic polymorphisms and MBI severity. METHODS: We included 62 aMCI-AD participants and 50 CN older adults from the Czech Brain Aging Study. The participants underwent neurological, comprehensive neuropsychological examination, APOE and BDNF genotyping, and magnetic resonance imaging. MBI was diagnosed with the Mild Behavioral Impairment Checklist (MBI-C), and the diagnosis was based on the MBI-C total score ≥ 7. Additionally, self-report instruments for anxiety (the Beck Anxiety Inventory) and depressive symptoms (the Geriatric Depression Scale-15) were administered. The participants were stratified based on the presence of at least one risk allele in genes for APOE (i.e., e4 carriers and non-carriers) and BDNF (i.e., Met carriers and non-carriers). We used linear regressions to examine the associations. RESULTS: MBI was present in 48.4% of the aMCI-AD individuals. Compared to the CN, aMCI-AD was associated with more affective, apathy, and impulse dyscontrol but not social inappropriateness or psychotic symptoms. Furthermore, aMCI-AD was related to more depressive but not anxiety symptoms on self-report measures. Within the aMCI-AD, there were no associations between APOE e4 and BDNF Met and MBI-C severity. However, a positive association between Met carriership and self-reported anxiety appeared. CONCLUSIONS: MBI is frequent in aMCI-AD and related to more severe affective, apathy, and impulse dyscontrol symptoms. APOE and BDNF polymorphisms were not associated with MBI severity separately; however, their combined effect warrants further investigation.
Keywords: Brain-Derived Neurotrophic Factor; Alzheimer’s disease; Genotype; polymorfismus genetický; kognitivní dysfunkce; Alzheimerova nemoc; Alzheimer Disease; Aged; senioři; Cognitive Dysfunction; mozkový neurotrofický faktor; Polymorphism, Genetic; Neuropsychological Tests; Mild behavioral impairment; lidé; apolipoproteiny E; Humans; Mild cognitive impairment; genotyp; neuropsychologické testy; Neuropsychiatric symptoms; Apolipoproteins E